2022
DOI: 10.1021/acs.jafc.1c08029
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Index for the Fat Fraction between Breast Milk and Infant Formulas

Abstract: The similarity of the fat fraction in infant formulas rich in either bovine milk fat (MF) or vegetable oil (VO) to breast milk was evaluated by analyzing their lipid composition. Milk fat-rich formulas were highly similar (average similarity index 0.68) to breast milk compared to the VO-rich formulas (average similarity index 0.56). The highest difference in the indices was found in the contents of cholesterol (0.66 vs 0.28 in MF-and VO-rich formulas, respectively, on average) and polar lipids (0.84 vs 0.53), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…It was reported that C18:1/C16:0/C18:1 (OPO) and C18:1/C16:0/C18:2 (OPL) were the major components in human milk, with 20%–40% of the total TAG, and they played an important role for the growth of infants (Zhao et al., 2018; Zhu et al., 2021; Lan et al., 2022). However, the percentage of OPO and OPL was low in infant formula based on cow milk; many manufacturers want their concentration to be close to that of human milk and so take some measures, such as adding soybean oil and palm oil (Zou et al., 2016; Hageman et al., 2019; Hokkanen et al., 2022). However, the TAG molecular species was different in vegetable oils and human milk; it is necessary to find other ingredients to substitute the vegetable oils, such as dairy milk fat and goat milk fat.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that C18:1/C16:0/C18:1 (OPO) and C18:1/C16:0/C18:2 (OPL) were the major components in human milk, with 20%–40% of the total TAG, and they played an important role for the growth of infants (Zhao et al., 2018; Zhu et al., 2021; Lan et al., 2022). However, the percentage of OPO and OPL was low in infant formula based on cow milk; many manufacturers want their concentration to be close to that of human milk and so take some measures, such as adding soybean oil and palm oil (Zou et al., 2016; Hageman et al., 2019; Hokkanen et al., 2022). However, the TAG molecular species was different in vegetable oils and human milk; it is necessary to find other ingredients to substitute the vegetable oils, such as dairy milk fat and goat milk fat.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies indicate a significant disparity in the PL composition, content, and micromorphology between commercial IF and human milk. 134 Although PLs account for a relatively low percentage of total lipids in human milk, their pivotal functional role in facilitating infant growth and development is evident from the above findings. The diversity of PL subclasses and molecular species directly influences the spectrum of PL functions.…”
Section: Simulation Of Human Milk Plsmentioning
confidence: 97%
“…The model used to evaluate the similarity between HMF and HMFS was first established by Wang et al (2010) to analyze the similarity between FAs and Sn-2 FAs in HMF and HMFS based on the reduction principle, and Hokkanen et al ( 2022) reported another evaluation model based on the Bray-Curtis index [17,18]. In this study, according to the human milk data reported in our previous study [3], software based on C++ was set up, and it was used to calculate the different formulas of mixed vegetable oils according to the evaluation model.…”
Section: Introductionmentioning
confidence: 99%